LC–MS/MS of permethylated N‐glycans derived from model and human blood serum glycoproteins. Issue 11 (5th April 2016) - Hu, Yunli; Shihab, Tarek; Zhou, Shiyue; Wooding, Kerry; Mechref, Yehia
Abstract : LC–MS/MS is one of the most powerful tools for N‐glycan structure elucidation; however, it is still challenging to identify some glycan structures with low abundance. In this study, we investigated the chromatographic behavior of permethylated N‐glycans. The relationship between retention times versus molecular weight of dextran, dextrin, and model glycans was investigated. Also, the nonpolar surface area of glycans was calculated and compared to their experimental retention times. Both retention time and nonpolar surface area trends are similar when the intermolecular interaction is included in the calculation. Moreover, retention time corresponds to glycan types and branch types. The N‐glycans analysis model, which combines high mass accuracy and retention time, was applied to confirm serum N‐glycans. In total, there were 78 N‐glycan compositions identified. A linear relationship between retention times and molecular weights were observed for each subgroup of glycan structures, for example, R 2 value for complex N‐glycans was determined to be > 0.98. Moreover, the retention time could be further applied to distinguish between structural isomers as well as linkage isomers. MS/MS data were used to confirm the structural isomers.